BALINESE CULTURE IN THE ARCHITECTURE OF THE LOBBY AND RESTAURANT at the Royal Pita Maha Resort in Ubud, Bali - Alwin Suryono (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2023)
Abstract: This paper aims to describe the physical elements of the lobby architecture - the Royal Pita Maha resort restaurant, and furthermore to reveal the meaning of Balinese culture. According to its method, the architectural object is expressed as 'physical existence', subsequently 'aspects of purpose', and finally 'essence' in the form of Balinese cultural meaning. The shape of the resort gate is the result of re-interpretation and improvisation of the past Puri Ubud gate. The lobby architecture is the result of re-interpretation and improvisation of the Balinese traditional public building with modern construction, manifesting the harmony of past-present life. The roof is more special than the others, representing the 'three layers of nature' in Balinese culture, open space and utilizing local resources referring to the 'harmonies of nature'. The layout of the continuous lobby - restaurant towards the South - North is adapted to the condition of the original land and utilizes local natural resources, standing for 'harmonies of local nature'. The re-interpretation of Balinese Traditional communal public building architecture with modern construction patterns means 'harmony of life' between the past and present. Once again, the roof is more outstanding than the other parts, referring to the 'three layers of nature.Keyword: Balinese culture, meaning, harmony.